Postbuckling response of functionally graded hybrid composite plates under combined uniaxial compression and in-plane shear loads - Vummadisetti, Sudhir; Singh, S.B. (Journal of Structural Engineering, 2024)
The postbuckling response of functionally graded hybrid composite plates subjected to combined uniaxial and inplane shear loading conditions is numerically investigated in the present study. The finite element formulation-based software ABAQUS has been used for the numerical study. Eigen buckling analysis and Tsai-Hill failure criteria are used to determine critical buckling and first ply failure loads, respectively. Functionally graded composite plates with and without cutouts are considered for the study. Five different shapes and three different sizes of cutouts at the center of the plate have been taken to examine the response under the combined in-plane loads. Effect of (0/90)4s, (+45/-45)4s, and (+45/-45/0/90)2s fiber stacking sequences are also examined. It is shown that, diamond-shaped cutout of small size among the cutouts performs better in terms of buckling and first ply failure loads of the plates under compressive loads combined with negative in-plane shear load. The (+45/-45)4s stacking sequence has the highest buckling and failure loads in comparison to other layup sequences.